World Music Festivals and Tourism – A Case Study of Serbia's Guca Trumpet Festival - Gligorijevic J (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
From its foundation in 1961 until the present day, the Guca trumpet festival has undergone significant transformations. Setting out as a small-scale cultural revival of Serbian brass orchestra tradition held annually in the village of Guca in the Dragacevo region of western Serbia, the festival has evolved over time into a great World Music spectacle. Disputes about the interpretation and representation of the national past and musical heritage have long been induced in public by the unsettled political situation in Serbia and by the festival's gradual integration into the global music industry and cultural tourism market. In consequence, the festival's relationship to issues of authenticity, tradition preservation, globalization impact, and representation politics continues to be viewed and discussed through familiar dichotomies. Using the interrelated theoretical models from World Music and cultural tourism studies, this paper aims to explore the reasons for the festival's prominent status in national cultural policies, as well as the contradictory meanings that it has generated in a variety of discourses.